2006
DOI: 10.1182/blood-2006-04-019588
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of expression of aquaglyceroporin 9 with arsenic uptake and sensitivity in leukemia cells

Abstract: Arsenic trioxide (As 2 O 3 ) is highly efficacious in acute promyelocytic leukemia (APL). Aquaglyceroporin 9 (AQP9) is a transmembrane protein that may be involved in arsenic uptake. In 10 of 11 myeloid and lymphoid leukemia lines, quantitative polymerase chain reaction (Q-PCR) and Western blotting showed that AQP9 expression correlated positively with As 2 O 3 -induced cytotoxicity. As a proof-of-principle, transfection of EGFPtagged AQP9 to the hepatoma line Hep3B, not expressing AQP9 and As 2 O 3 insensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
131
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 33 publications
4
131
1
Order By: Relevance
“…Our results are consistent with a role for AQP9 in arsenite export, which is in contrast to previous studies of cultured cells (7,(12)(13)(14)(15). However, our studies do not exclude a role for AQP9 in arsenite import.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Our results are consistent with a role for AQP9 in arsenite export, which is in contrast to previous studies of cultured cells (7,(12)(13)(14)(15). However, our studies do not exclude a role for AQP9 in arsenite import.…”
Section: Discussioncontrasting
confidence: 57%
“…Excretion of arsenic in urine and feces of AQP9-null mice is greatly reduced. Although AQP9 is known to facilitate uptake of arsenite by single cells in culture (12)(13)(14)(15), our studies cause us to propose that AQP9 also facilitates in vivo arsenic excretion by the liver, thereby providing partial protection against arsenic toxicity.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The transmembrane protein aquaglyceroporin 9 (AQP9) allows more ATO to enter into cells. 54 ATO has been proposed as a therapy for nonAPL leukemias, 43,55 and for solid tumors. 55 This approach has been limited by the higher ATO doses required to induce apoptosis in nonAPL cells.…”
Section: Discussionmentioning
confidence: 99%
“…NB4, the first APL cell line with t(15;17), was established from marrow samples obtained from a patient with APL receiving retinoic acid (8). NB4 has been widely used to investigate the cellular and molecular mechanisms of ATRA and ATO (9)(10)(11)(12)(13)(14). Cell biology studies using NB4 and APL blasts obtained from patients have revealed that ATO exerts dose-dependent dual effects on APL cells.…”
Section: Introductionmentioning
confidence: 99%